Kiedy poznajemy prawdziwych przyjaciół? Znane przysłowie w dawnej i współczesnej polszczyźnie - Młynarczyk, Ewa (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2025)
The paper is devoted to the history of one proverb of ancient origin. The purpose of the analysis is to recreate the processes of developing its canonical form and variability, as well as some innovations that it is subjected to in the contemporary Polish language. The material base comprises contexts excerpted from language corpora and other examples found in various texts. Also, Internet memes were taken into consideration, in which case the creators use the discussed paremic unit for specific linguistic games, including the so-called anti-proverbs. Contemporary textual uses confirm strong stabilization of one variety of the proverb, which was developed and spread by Adam Mickiewicz, and has frequently been repeated as a whole. The preservation and vitality are also proven by innovative lexical-semantic transformations in which components are replaced and some elements are added or reinterpreted. Some transformations of the proverb are also used to challenge the judgment that it contains.